Viral metatranscriptomic approach to study the diversity of virus(es) associated with Common Bean (Phaseolus vulgaris L.) in the North-Western Himalayan region of India - Rashid, Shahjahan; Wani, Farhana; Ali, Gowhar; Sofi, Tariq A.; Dar, Zahoor Ahmed; Hamid, Aflaq (Frontiers in Microbiology, 2022)
Plant viruses are a major threat to legume production worldwide. In recent years, new virus strains have emerged with increasing frequencies in various legume cropping systems, which demands the development of cutting-edge virus surveillance techniques. In this study, we surveyed the common bean fields of Kashmir valley for virus infection using a total of 140 symptomatic and non-symptomatic leaf samples collected from different locations. The genetic diversity of viruses was examined by high-throughput sequencing (HTS) with three viruses being identified, namely, Bean Common Mosaic Virus (BCMV), Bean Common Mosaic Necrosis Virus (BCMNV), and Clover Yellow Vein Virus (ClYVV). BCMNV and ClYVV are new reports from India. De novo assembly of transcriptome constructed near-complete genomes of these viruses. RT-PCR results confirmed the presence of these viruses with an emerge incidence of 56. 4% for BCMV, 27.1% for BCMNV and 16.4 for ClYVV in the valley. Several samples were found to contain multiple virus infections with BCMV being the most predominant. Recombination events were detected in the genomes of BCMV and ClYVV, but not BCMNV. Phylogenetic and pairwise identity matrix evidence suggests viral import from multiple countries. Our results demonstrate that HTS followed by multiplex PCR assay is a simple, rapid, and reliable approach for simultaneous diagnosis of plant viruses.